Respiratory distress syndrome in preterm infants of less than 32 weeks: What difference does giving 100 or 200 mg/kg of exogenous surfactant make?. Issue 9 (27th May 2022) - Lanciotti, Lucia; Correani, Alessio; Pasqualini, Matteo; Antognoli, Luca; Dell'Orto, Valentina G.; Giorgetti, Chiara; Colombo, Sara; Palazzi, Maria L.; Rondina, Clementina; Burattini, Ilaria; Carnielli, Virgilio P.
Abstract: Background: Surfactant dosing and effective delivery could affect continuous positive airways pressure (CPAP)‐failure. Nevertheless, information on exogenous surfactant dosing with current administration methods is limited. Objective: To describe the effect of 100 or 200 mg/kg of surfactant as first‐line treatment of respiratory distress syndrome in preterm infants of less than 32 weeks gestation. Study Design: A retrospective single‐center cohort study comparing two epochs, before and after switching from 100 to 200 mg/kg surfactant therapy. Results: Six hundred and fifty‐eight of the 1615 infants of less than 32 weeks were treated with surfactant: 282 received 100 mg/kg (S‐100) and 376 received 200 mg/kg (S‐200). There were no differences between S‐100 and S‐200 in perinatal data including prenatal corticosteroids, medication use, age at first surfactant administration and respiratory severity before surfactant. The S‐200 vs. S‐100 had fewer retreatments (17.0% vs. 47.2%, p < 0.001) and a shorter duration of oxygen therapy and mechanical ventilation (315 vs. 339 h, p = 0.018; 37 vs. 118 h, p = 0.000, respectively). There was no difference in postnatal corticosteroid use (S‐200 10.0% vs. S‐100 11.0%, p = 0.361). Bronchopulmonary dysplasia (BPD) was significantly lower in S‐200 vs. S‐100 when comparing either the 4 and 6‐year periods before and after the dose switch (29.4% vs. 15.7%, p = 0.003, and 18.7% vs. 27.3%, p = 0.024, respectively) Conclusions: The switch from 100 to 200 mg/kg was associated with a marked reduction in the need for surfactant redosing, respiratory support, and BPD. This information could be important when designing a study in the modern era of less invasive administration as surfactant dosing and its effective delivery may affect the outcome.